2017
DOI: 10.1590/1678-4324-2017160441
|View full text |Cite
|
Sign up to set email alerts
|

Piper gaudichaudianum Kunth: Seasonal Characterization of the Essential Oil Chemical Composition of Leaves and Reproductive Organs

Abstract: This study describes a comparative analysis of the essential oil (EO) chemical composition of leaves and reproductive organs (inflorescences and fruits) of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
0
14
1
Order By: Relevance
“…The main components found in the EOPad also differ with results obtained in previous studies for this species. Almeida et al [28] identified dillapiole (76%) as the main component of the EOPad, diverging with the result found in this study; however, it resembles the result found by Schindler and Heinzmann [29] who identified β-copaen-4-α-ol among the major constituents in the EOPg, a species that is part of the same genus of P. aduncum.…”
Section: Discussioncontrasting
confidence: 86%
“…The main components found in the EOPad also differ with results obtained in previous studies for this species. Almeida et al [28] identified dillapiole (76%) as the main component of the EOPad, diverging with the result found in this study; however, it resembles the result found by Schindler and Heinzmann [29] who identified β-copaen-4-α-ol among the major constituents in the EOPg, a species that is part of the same genus of P. aduncum.…”
Section: Discussioncontrasting
confidence: 86%
“…According to Schindler and Heinzmann [77] the literature on P. gaudichaudianum EOs reports a generic composition characterized by sesquiterpene hydrocarbons (22.5 to 36.4%), with smaller percentages of oxygenated sesquiterpenoids (0.2 to 5.8%), trace amounts of monoterpene hydrocarbons and no oxygenated monoterpenoids. However, the authors found in their analyses that the EOs from leaves and reproductive organs had a strikingly different composition, and were dominated by the phenylpropanoid class, and in particular by dillapiole, which in fresh leaves was at levels between 68.4% and 69.2%, and in the inflorescences between 83.1% and 87.5% [77]. Myristicin was also present in the reproductive organs in the range of 6.2 to 11.9%.…”
Section: Chemical Constituents Of the Essential Oils Of Piper Speciesmentioning
confidence: 99%
“…Myristicin was also present in the reproductive organs in the range of 6.2 to 11.9%. This high percentage of phenylpropanoids left less room for other constituents, but the main ones were α-humulene (13.3–37.5%), β-caryophyllene (10.4–19.3%), β-pinene (5.6–7.0%), ( E )-nerolidol (5.32–22.4%), β-caryophyllene (8.9%), bicyclogermacrene (7.4%), β-selinene (3.7–15.7%), α-selinene (8.9–16.6%), allo -aromadendrene (7.7%) and linalool (4.8%) [77]. See Table 17.…”
Section: Chemical Constituents Of the Essential Oils Of Piper Speciesmentioning
confidence: 99%
“…The conglomerate analysis (CA) of all the accessions was carried out with these descriptors from the agglomeration UPGMA hierarchical method (Unweighted Pair-Group Method using Arithmetic Averages), and the Euclidean distance as a measure of dissimilarity [23]. The accuracy of the classification of the PCA was integrated via discriminant analysis (DA) data and assessed the contribution of studied isoenzymatic systems, classification of accessions.…”
Section: Discussionmentioning
confidence: 99%